2006
DOI: 10.1159/000097453
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Vitamin A on Cytokine Secretion by Mononuclear Cells of Preterm Newborns and Adults

Abstract: Background: For a long time vitamin A has been known to be essential for immune defense of the organism and protection against infections. Vitamin A deficiency in children is associated with morbidity and mortality from infectious diseases which could be prevented and even alleviated by vitamin A supplementation. Moreover, this vitamin is involved in the modulation of immunological and inflammatory responses by regulation of cytokine production. The aim of the study was to compare the in vitro effect of vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Several studies have been conducted on vitamin A status in children with SCD and its influence on health status or the role of vitamin A status in lymphocyte proliferation and cytokine secretion in individuals and laboratory animals without SCD. [1][2][3]16,[28][29][30][31][32] The negative effect of suboptimal vitamin A status on immunity has been clearly demonstrated. In 2 studies conducted on blood lymphocytes obtained from healthy adult subjects without SCD, the addition of vitamin A (in the form of retinoic acid) to culture medium resulted in increased IL-2 secretion, lymphocyte proliferation, and dendritic cell maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on vitamin A status in children with SCD and its influence on health status or the role of vitamin A status in lymphocyte proliferation and cytokine secretion in individuals and laboratory animals without SCD. [1][2][3]16,[28][29][30][31][32] The negative effect of suboptimal vitamin A status on immunity has been clearly demonstrated. In 2 studies conducted on blood lymphocytes obtained from healthy adult subjects without SCD, the addition of vitamin A (in the form of retinoic acid) to culture medium resulted in increased IL-2 secretion, lymphocyte proliferation, and dendritic cell maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings are evident on the effect of vitamin A deficiency on the ability of individual's immune system to counteract pathogens. Moreover, this micronutrient is known to regulate antibody production via many pro and anti inflammatory modulators [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A exerts its anti-inflammatory action by suppressing the production of pro-inflammatory cytokines (83). Study showed that vitamin A has inhibitory effect on production of cytokines IL-1ra and IL-10 secretion (84). Supplementation with vitamin B (mainly B1, B2, B3, B5, B6, and B12) complex also exerts anti-inflammatory effects (85).…”
Section: Vitamins and Mineralsmentioning
confidence: 99%